1976
DOI: 10.1111/j.0954-6820.1976.tb06709.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological and Clinical Evaluation of Different Dialysate Delivery Systems

Abstract: In the period 1-74 four different dialysate delivery systems have been used in our department. 1 ) Central mixing of dialysate using tap water and a dialysate delivery line with "dead ends" resulting in stagnant dialysate. 2) Central mixing of dialysate with cold distilled water, otherwise equal to system 1. 3) Local mixing of dialysate with cold distilled water, delivered through a line with "dead ends" resulting in stagnant water. 4) Local mixing of dialysate with distilled water, cooled to 25°C just prior t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1982
1982
2004
2004

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 12 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…These two outbreaks, plus a European study (2), formed the basis for the dialysate bacteriological standard of 52,000 cfu/ml adopted by the Association for the Advancement of Medical Instrumentation (AAMI). The water standard of 5200 cfu/ml was an arbitrary value based on an anticipated one log increase in bacterial contamination as water is mixed with dialysate concentrate, heated, and circulated through the dialysis machine.…”
Section: Historical Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…These two outbreaks, plus a European study (2), formed the basis for the dialysate bacteriological standard of 52,000 cfu/ml adopted by the Association for the Advancement of Medical Instrumentation (AAMI). The water standard of 5200 cfu/ml was an arbitrary value based on an anticipated one log increase in bacterial contamination as water is mixed with dialysate concentrate, heated, and circulated through the dialysis machine.…”
Section: Historical Aspectsmentioning
confidence: 99%
“…There are data that pyrogenic reactions are related to the number of bacteria in dialysis fluids. Based on these studies, the AAMI guidelines for bacteria counts in water of ~2 0 0 cfu/ml (but not necessarily sterile) were developed (2). These recommendations have been accepted by the U S .…”
mentioning
confidence: 99%
“…It is also difficult to conceive of endotoxin micelles crossing the protein retentive membranes used for hemodialysis. Nevertheless, studies have shown a correlation between levels of bacterial contamination of dialysate and the incidence of pyrogenic reactions (10,22). Although endotoxins exist largely as micelles, these micelles are thought to be in equilibrium with some small concentration of free endotoxin.…”
mentioning
confidence: 99%